Xanthoma of Bone: A Case Report - Hasnae Guerrouj; Ayat Mouaden; Nouzha BenRais (Case Reports in Endocrinology)
Bone xanthoma is a rare disease due to the presence of cholesterol deposits in the bone. We report a case of a 56-year-old patient who was hospitalized in orthopedic department for fracture on the left humerus. Histological examination of bone biopsy performed at this site has objectified cholesterol deposits. Laboratory tests showed hypercholesterolemia with hypertriglyceridemia. The diagnosis of bone xanthoma was selected. The fracture was treated surgically. An initial bone scan revealed bone lesions localized especially at the humerus and femur. The patient was put under fenofibrate and statins. The evolution was marked by gradual regression of lesions in bone scans of control.